Variants of Haemophilia B - Elödi, Susan; Puskás, Éva (Thrombosis and Haemostasis, 1972)
Variants of haemophilia B were examined by antibody-neutralization technique and by the ox brain thromboplastin time method. On the basis of the presence or absence of anomalous factor IX and of prothrombin time, four variants of haemophilia B were discerned. It is shown that the prolongation of prothrombin time, measured in our cases, cannot be attributed to an inhibitor in the patients’ plasma.